Authoritarian criminology and the racial profiling debate in Canada: scientism as epistemic violence - Kitossa, Tamari (African journal of criminology and justice studies, 2014)
The scholarly debate about racial profiling in Canada centres on the attack or defence of methods and conclusions. To date, the scholarly literature in Canada has largely excluded the debate about racial profiling as itself a site of inquiry. Focusing on the 2003 Canadian Journal of Criminology and Criminal Justice (CJCCJ) special colloquy that responded to the Toronto Star’s claims that the Metro Toronto systemically engage in racial profiling, I use Agozino’s critique of imperialist reason and Tauri’s concept of authoritarian criminology to demystify how the CJCCJ and its authoritarian respondents engaged in a positivistic agenda setting ‘discursive formation’ rooted in scientific rationality. Further, I draw on the death of (white) sociology tradition to demonstrate that this discursive formation, rooted in the pretensions of scientific rationalism, constitutes both epistemic violence toward the colonized and people ‘of color’ while certifying scientific veracity as an embodied property of White middle class and system serving males. The tactic of criminological and legal positivists in this debate is to disqualify, subordinate, ridicule and ultimately invalidate the truth claims of racial profiling victims.